Inclusion of Students with Visual Impairment in a Regular University Setting: Experiences, Challenges, and Coping Mechanisms - Bhalalusesa, Elizabeth (Papers in Education and Development, 2016)
Currently, there has been a gradual increase in the number of visually impaired students being admitted to higher learning institutions in Tanzania where they are obliged to learn in settings designed for students without disabilities. This paper attempts to provide an inner understanding of how these students actually learn, the challenges they experience in the process of learning, and the strategies they use to cope with these challenges. The paper is based on a study conducted using 12 visually impaired students studying for a degree at a university in Tanzania. The findings of this study demonstrate that students with visual impairment are able to learn like students with no such disability. However, these students have additional needs attributable to their disability, which make their daily tasks as students complicated because of their lack of sight. Apart from individual personal efforts, visually impaired students have to struggle to seek and make use of available support networks to learn and perform to the best of their ability. Therefore, sensitivity of the teaching as well as non- teaching staff is necessary to create an equitable, safe and friendly learning environment where each learner feels valued, accepted and included. Key words: Higher education, inclusive education, visual impairment